THE ROLE OF CORPORATE SOCIAL RESPONSIBILITY IN COMMUNITY’S SUSTAINABLE DEVELOPMENT AROUND MINING PROJECT - Mongi, Milianithya S. (FEB Universitas Sam Ratulangi Manado, 2013)
Devil may care. The implementation of Corporate Social Responsibility in mining company has become a popular issue today. This research examines about the implementations of Corporate Social Responsibility of PT. Leighton Contractors Indonesia (LCI) – Toka Tindung Gold Mine Project and its role in Sustainable Development of Community near the mining project. The theories used are corporate social responsibility and sustainable development. This research uses qualitative method with six informants from the community and 2 informants who are the employees of PT. LCI – Toka Tindung. The results of this research are community around mining project are not prosperous, although PT. LCI – Toka Tindung does well in the implementation of CSR, the community thinks that the assistance given by PT. LCI – Toka Tindung is not enough, but they do contribute to the society. The implementation of CSR by PT. LCI also affects the sustainable development by training the local community. Keywords: corporate social responsibility, sustainable development